Ultrasonographic prediction of antepartum deterioration of growth‐restricted fetuses after late preterm. Issue 6 (2nd April 2018) - Yamamoto, Ryo; Ishii, Keisuke; Nakajima, Erika; Sasahara, Jun; Mitsuda, Nobuaki
Abstract: Aim: To examine the predictive value of ultrasound parameters for antepartum non‐reassuring fetal status (NRFS) in fetal growth restriction (FGR) cases after late preterm. Methods: Retrospective review of singleton FGR cases before 37 weeks gestation who delivered after 34 weeks gestation was performed. The association between ultrasound parameters that was assessed from 34 to 36 weeks gestation and the development of antepartum NRFS that was diagnosed by nonstress test and biophysical profile was analyzed by using multivariate Cox proportional hazards analyses. Results: A total of 214 patients were included in final data analyses. Antepartum NRFS occurred in 23 cases (10.7%) including five cases of placental abruption. Lower standard deviation (SD) of estimated fetal weight (EFW), lower cerebroplacental ratio (CPR) and the presence of oligohydramnios were independently associated with antepartum NRFS. The prevalence of antepartum NRFS was highest (50.4%) in the group of EFW ≤−2.5 SD with CPR ≤1.45. Conclusion: Ultrasound parameters of lower SD of EFW, lower CPR and oligohydramnios were predictive for antepartum NRFS in FGR after late preterm.